The last child - Hart, John, 1965- (Minotaur Books, 2009)
After his twin sister Alyssa disappears, thirteen year-old Johnny Merrimon is determined to find her. When a second girl disappears from his rural North Carolina town, Johnny makes a discovery that sends shock waves through the community in this multi-layered tale of broken families and deadly secrets.